Youth Baseball Pitch Counts Vastly Underestimate High-effort Throws Throughout a Season. Issue 7 (August 2020) - Wahl, Elizabeth P.; Pidgeon, Tyler S.; Richard, Marc J.
Abstract : Background: The primary purpose of this study was to compare the number of pitches thrown by youth baseball players under the official league guidelines versus the number of "high-effort" throws recorded by a validated digital sensor worn by the players during a season. Methods: In total, 11 and 12-year-old youth baseball players from a single league were provided an elbow sleeve and sensor to wear each time they threw a baseball for an entire baseball season. The sensor tracked total throws and pitch-equivalent high-effort throws for the season. Official pitch counts were collected at each game from the official scorekeepers. Results: A total of 19 players participated in the study. The sensor-determined mean total throw count (1666.2±642.2) and mean high-effort throw count (576.9±329.3) per player were both significantly higher, P <0.0001 and P =0.02, respectively, than the mean official pitch count (168.1±122.4). Conclusions: Our findings demonstrate that youth players make significantly more total throws and high-effort, or pitch-equivalent, throws, than what is recorded by the official pitch counts. Further research is needed to determine a safe annual "throw count" for young throwing athletes and to determine which types of throws, in addition to pitches, put youth throwers at risk for injury. Level of Evidence: Level IV.